Funding an unfulfilled promise: First Nations jurisdiction over education in British Columbia - LeBlanc, Vanessa Nancy (2015)
In 2006, the First Nations Education Steering Committee signed an agreement with Canada and British Columbia to secure First Nations jurisdiction over education in BC—the Education Jurisdiction Framework Agreement. This agreement marked an important point in First Nations in British Columbia’s efforts to create an education system under their own control. Despite initial optimism, progress on the implementation of the agreement stalled over funding. Given this stalemate, the purpose of this study is two-fold: first, to provide a better understanding of the current state of education jurisdiction negotiations in British Columbia; and second, to examine education funding models to assess their appropriateness for funding First Nations’ education jurisdiction. Formula and needs-based funding models are examined and assessed using a values-based criteria analysis. An appropriate model to provide adequate funding and ensure an equitable education system for First Nations learners is identified and recommended.